Reevaluating Sail Propulsion for Traditional Fishing Vessels: Economic and Environmental Benefits of The 'Ijon-Ijon' Boat in Lamongan, East Java (Faculty of Fisheries and Marine Science, Brawijaya University, 2025)
This study aimed to evaluate the techno-economic feasibility of reintroducing sail propulsion on the traditional